(untitled) (Research, Society and Development, 2024)
Thermometric evaluation is extremely important in the routine of small animal medical clinics, and often the restraint required for precise and safe measurement, whether using a rigid mercury column thermometer or a digital thermometer, can lead to animal stress. In an attempt to minimize this stressor, this study proposed the use of an infrared thermometer, which became very popular during the COVID-19 pandemic for screening humans with fever for access to public collective spaces. This project aimed to measure the body temperature of dogs using two different methods and compare the efficiency of these methodologies. For this, the traditional rectal measurement with a digital thermometer was compared with the measurement of the external temperature of the anus and the ear canal of 100 dogs in the clinical routine of a veterinary clinic in Rio de Janeiro. It was estimated that on average the temperature in the ear canal is 1.2°C lower than the rectal temperature, and in the anus, it is 1.9°C lower than the rectal temperature. However, the correlation coefficient was low (<0.4) in both approaches. It can be concluded that the use of an infrared thermometer did not prove to be a reliable alternative to replace traditional thermometry.